Analysis of an unconventional cycle as a new comparison standard for practical heat engines:: the circular/elliptical cycle in T-S diagram - Sahin, B; Ust, Y; Kodal, A; Yilmaz, T (JOHN WILEY & SONS LTD, 2004)
An unconventional cycle analysis in the T-S diagram has been carried out and the cycle characteristics such as thermal efficiency, work density (defined as the ratio of the network output to the maximum volume in the cycle), maximum volume and maximum pressure are determined. The obtained results for the unconventional cycle are compared with those of the Carnot cycle. It is proposed that the analysed unconventional cycle may be used as a better comparison standard than the Carnot cycle for practical heat engines when both size and thermal efficiency are considered. Copyright (C) 2004 John Wiley Sons, Ltd.
Keywords: work density; heat engines; unconventional cycle; MAXIMUM POWER-DENSITY; JOULE-BRAYTON ENGINE; ECOLOGICAL OPTIMIZATION; PERFORMANCE ANALYSIS; CARNOT CYCLES; EFFICIENCY; CRITERION; Energy & Fuels; Nuclear Science & Technology